2017
DOI: 10.1002/2016gc006763
|View full text |Cite
|
Sign up to set email alerts
|

The role of mud volcanism and deep‐seated dewatering processes in the Nankai Trough accretionary prism and Kumano Basin, Japan

Abstract: Circulation of water at moderate depths in subduction zones is dominantly driven by clay mineral dehydration over distinct pressure and temperature gradients. The signature of these dehydration reactions is found in mud volcano pore waters, however, it is largely unknown, how much of the deep‐seated fluids are emitted at mud volcanoes. To unravel this relation for the region off the Kii Peninsula, Japan, we calculated the water volume that is subducted in the Nankai Trough using input data from IODP holes C001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 119 publications
2
19
0
Order By: Relevance
“…Nishio et al [16] inferred that Li isotope ratios in porewater of the drilled core from KMV#5 indicate temperatures as high as 310 • C, which is significantly higher than the S-I conversion temperature range of 60-150 • C. They suggested that a portion of fluid was derived from the periodic injection of deep-seated fluid accumulated in the corner of the serpentinized forearc mantle wedge, transported upward along a thrust fault [16]. Modeling of the water circulation in mud volcanoes of the Kumano basin has suggested that the fluids in the mud volcano sediment are derived by S-I transformation in the accretionary prism and decomposition of basaltic saponite in the subducting slab (Figure 8) [13]. In sum, the fluid in the mud volcanoes of the Kumano basin appears to originate in or beneath the accretionary prism underlying the Kumano forearc basin sediment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nishio et al [16] inferred that Li isotope ratios in porewater of the drilled core from KMV#5 indicate temperatures as high as 310 • C, which is significantly higher than the S-I conversion temperature range of 60-150 • C. They suggested that a portion of fluid was derived from the periodic injection of deep-seated fluid accumulated in the corner of the serpentinized forearc mantle wedge, transported upward along a thrust fault [16]. Modeling of the water circulation in mud volcanoes of the Kumano basin has suggested that the fluids in the mud volcano sediment are derived by S-I transformation in the accretionary prism and decomposition of basaltic saponite in the subducting slab (Figure 8) [13]. In sum, the fluid in the mud volcanoes of the Kumano basin appears to originate in or beneath the accretionary prism underlying the Kumano forearc basin sediment.…”
Section: Discussionsupporting
confidence: 73%
“…Because our porewater samples from KMV#10 show the same trends in δ 18 O and δD values with respect to Cl -concentrations, KMV#10 also was affected by water derived from clay mineral dehydration. Indeed, this process has previously been reported for other mud volcanoes in the Kumano basin (KMV#2-11) [13].…”
Section: Discussionmentioning
confidence: 98%
“…In the Kumano Basin, 13 mud volcanoes have been observed at anticlines along the landward megasplay faults ( Fig. 1 , B and C) ( 17 – 20 ). Chemosynthetic macrofaunal communities occur at seep environments on the summits of these features ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment compaction and mineral dehydration are the most important mechanisms for fluid generation and circulation in an accretionary prism 6,7 . In essence, both mechanisms are driven by the increasing pressure and temperature associated with sediment burial and deformation.…”
mentioning
confidence: 99%